The Degree of Employment of Teachers of the General Education Stage of the Theory of Brain-based Learning Based on some Variables - Mohammad Baker Nofal (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: The purpose of the current study is to investigate the level of general education teachers' employment of brain-based learning theory in light of some variables. Methods: Descriptive Survey Research has been used. The study sample consists of (410) participants; (110) male teachers and (300) female teachers. To achieve the study objectives, the Brain-Based Learning Survey is used after verifying its psychometric characteristics. Results: The results indicate that the degree of using brain learning by the general education teachers is on average across all three domains and on the total score. The analysis of variance showed statistically significant differences in gender in domain 2 (beliefs) and 3 (practice) and the total score of the use of the general education teachers' measurement scale for brain-based learning. All differences are for females. The impact of ETA was low on the gender variable in beliefs (0.028) and in practice (0.013) and the total score (0.024). There are no statistically significant differences due to variable experience and scientific qualification. Conclusions: The study concluded with a set of recommendations, of which the most significant is inclusion of the theory principles in the academic curriculum and training teachers on how to use it effectively. Also, studies related to using the principles of brain-based learning theory in light of new variables are needed.